Etta and Otto and Russell and James : a novel - Hooper, Emma (Simon & Schuster, 2015)
Embarking on a more than 3,000-kilometer walking journey from rural Canada to the East coast so that she can see the ocean for the first time in her life, an octogenarian woman has experiences that blur her perspectives between illusion, memory and reality.